2010
DOI: 10.1107/s0021889810050077
|View full text |Cite
|
Sign up to set email alerts
|

A synchrotron tomographic energy-dispersive diffraction imaging study of the aerospace alloy Ti 6246

Abstract: A titanium alloy sample (#6246) containing a linear friction weld has been imaged nondestructively using tomographic energy‐dispersive diffraction imaging (TEDDI). The diffraction patterns measured at each point of the TEDDI image permitted identification of the material and phases present (±5%). The image also showed the preferred orientation and size–strain distribution present within the sample without the need for any further sample preparation. The preferred orientation was observed in clusters with avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…1) (Harding et al, 1985(Harding et al, , 1987Kleuker et al, 1998). Using polychromatic Laue diffraction, two-and three-dimensional microscopy images have been successfully obtained on well crystallized thin films and alloys (Tamura et al, 2002;Budai et al, 2003;Larson et al, 2002;Beale et al, 2007;Cernik et al, 2011;Hofmann et al, 2012). Using monochromatic diffraction, it has been shown that three-dimensional images of well crystallized samples can also be reconstructed, on the basis of the diffracted beam paths of each grain (considered as single crystals).…”
Section: Combined Diffraction/scattering and Tomography Methodsmentioning
confidence: 99%
“…1) (Harding et al, 1985(Harding et al, , 1987Kleuker et al, 1998). Using polychromatic Laue diffraction, two-and three-dimensional microscopy images have been successfully obtained on well crystallized thin films and alloys (Tamura et al, 2002;Budai et al, 2003;Larson et al, 2002;Beale et al, 2007;Cernik et al, 2011;Hofmann et al, 2012). Using monochromatic diffraction, it has been shown that three-dimensional images of well crystallized samples can also be reconstructed, on the basis of the diffracted beam paths of each grain (considered as single crystals).…”
Section: Combined Diffraction/scattering and Tomography Methodsmentioning
confidence: 99%
“…5153 Energy-dispersive diffraction tomography 54 has also been performed to track sulfate attack of Portland cement 55 and to study Ti alloys. 56 …”
Section: Examplesmentioning
confidence: 99%
“…EasyDD has been used in a number of key studies such as [5, 7, 10--14]. It has also been used by the High Energy X-Ray Imaging Technology (HEXITEC) project for the development of multi-pixel 2D X-ray detectors [3,9,16]. However, in this section we present a brief account of a nickel chloride catalysis system study as a show case for the use of EasyDD in processing and analyzing powder diffraction data.…”
Section: Case Studymentioning
confidence: 99%